Formalizing clientelism in Kenya: From Harambee to the Constituency Development Fund - K. Ochieng' Opalo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Why does clientelism persist? What determines how politicians signal responsiveness or fulfil their campaign promises? Existing works assume that politicians choose the most successful means of winning votes-either through targeted patronage/clientelism or programmatic policies. However, the empirical record shows high levels of persistence of the nature of the relationship between voters and politicians. Both politicians and voters are not always able to unilaterally change what campaign promises are achievable and therefore deemed credible. Using evidence from the Constituency Development Fund in Kenya, this paper shows that the nature of the relationship between voters and politicians is historically constructed and governed by a combination of state capacity and established expectations about what a 'good' politician does. In short, clientelism persists when it is the most credible means of fulfilling campaign promises. The paper also shows how politicians may be incentivized to reform political practice away from clientelism. The findings herein increase our understanding of the origins and persistence of clientelism in low-income states and potential avenues for reform towards programmatic politics.
Keywords: 330; constituency service; legislative politics; Constituency Development Fund; Kenya